Analysis of account representatives on taxpayers in lampung province using structural equation model - Rinaldi, Achi; Devi, Yulistia; Widyastuti, Rany (Desimal: Jurnal Matematika, 2024)
Tax policy was crucial as it influenced economic growth. The tax rate was determined by the income level of the population. To improve tax administration quality, the government developed infrastructure and enhanced the services of tax office employees. By gathering taxpayers' opinions, the quality of services and oversight could be analyzed to refine tax administration performance in the future. This study aimed to determine the effect of service quality, consultation, and supervision by account representatives on taxpayer compliance. It employed a quantitative approach, utilizing various statistical tests with SEM analysis. The population consisted of 97,714 active taxpayers registered at six KPP Pratama offices in Lampung in 2022. The sample size was determined using the Slovin formula, resulting in 100 taxpayers selected through Simple Random Sampling. Data were collected directly from active taxpayers using a questionnaire as the research instrument. The findings revealed that the variables of service quality, consultation, and supervision by account representatives had a significant influence on taxpayer compliance, both partially and simultaneously.